Pesticide exposure and cancer: an integrative literature review - Thaís Bremm Pluth; Lucas Adalberto Geraldi Zanini; Iara Denise Endruweit Battisti (Centro Brasileiro de Estudos de Saúde, 2019)
ABSTRACT We conducted an integrative literature review of published studies on pesticide and cancer exposure, focusing on farmers, rural population, pesticide applicators, and rural workers. The Medline/PubMed was used as searching database. After the retrieval, 74 articles were selected according to pre-established criteria, which design involved 39 case-controls, 32 cohorts, 2 ecological ones, and 1 cross-sectional. Among them, 64 studies showed associations between pesticides and cancer while 10 did not find any significant association. The studies found 53 different types of pesticides significantly associated with at least one type of cancer and 19 different types of cancers linked to at least one type of pesticide. Although few studies presented contradictory results, the sole fact of being a farmer or living near crops or high agricultural areas have also been used as a proxy for pesticide exposure and significantly associated with higher cancer risk. The literature well illustrates the case of prostate cancer, Non-Hodgkin lymphoma, leukemia, multiple myeloma, bladder and colon cancers. Studies are recommended to further investigate the relationship between pesticide and neoplasm of testis, breast, esophagus, kidney, thyroid, lip, head and neck, and bone.